Design of a climbing robot platform with protection device. (4th July 2017) - Altaf, Meteb; Ahmad, Eball; Xu, Yaru; Liu, Rong; Li, Yang; Na, Han
In this article, a new wall-climbing robot platform with protection devices for city inspection is developed. After an overall structural introduction, the main protection devices of the robot are described in detail, including the support frame, the Ethylene Vinyl Acetate (EVA) shell, and the airbag. The support frame plays the roles of chassis and protection framework, so integrative and lightweight design is required. The EVA shell covers the support frame, and it protects the robot from overturn falling down from the wall. The airbag is designed both for sealing and protection. The mechanical model of the airbag is established based on the engineering thermodynamics theory and is used for force analysis when robot falls down on the ground. In addition, two-level distributed control system is designed to achieve the control of fan speed, straight moving, differential steering, position servo, and video transmission. To verify the feasibility of the climbing robot, many experiments are conducted, that is, experiments of movement, load capacity, adaptability to the wall surfaces, endurance, camera, sensor, and antithrow. The results show that the actual working performance of the climbing robot is favorable, thus providing a train of thought and inspiration for the antithrow design of climbing robot.